2017
DOI: 10.1021/acs.cgd.7b00785
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Thermosalient Effect of N′-2-Propylidene-4-hydroxybenzohydrazide Accompanied by an Immense Negative Compressibility: Structural and Theoretical Arguments Aiming toward the Elucidation of Jumping Phenomenon

Abstract: The temperature-induced reversible phase transition of N′-2-propylidene-4-hydroxy­benzo­hydrazide from the polymorphic Form II to Form III, and vice versa, is accompanied by the dramatic change of the macroscopic dimensions of the crystal which resulted in the pronounced mechanical motion (jumping) during the phase transition. Prior to the phase transition, the extremely large uniaxial negative thermal expansion along one crystal axis (b axis) was observed, together with the positive thermal expansions along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…The volume change corresponding to the phase transition was 0. In cases of relatively small structural changes, the origin of large mechanical effects can be sought in the anisotropy of strain 2,7,[44][45][46] . In fact, strain accompanying the phase transition in TBB is strongly anisotropic (Table 2, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume change corresponding to the phase transition was 0. In cases of relatively small structural changes, the origin of large mechanical effects can be sought in the anisotropy of strain 2,7,[44][45][46] . In fact, strain accompanying the phase transition in TBB is strongly anisotropic (Table 2, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The absolute strain values at the moment of the phase transition on heating from 303 to 313 K are approximately 14 times higher in the direction of principal axis 1, approximately 5 times higher in the direction of principal axis 2, and approximately 13 times higher in the direction of principal axis 3, as compared to the corresponding strain values achieved on heating from 293 to 303 K before the phase transition ( Figure 4). In order to achieve the same values of structural strain without the phase transition, it would be necessary to heat the crystal to 370-420 K. Such anisotropic strain accompanying a phase transition is typical for thermosalient materials 2,7,[44][45][46] . While it has been noted previously that the β-γ transition is endothermic, it remains interesting to examine the pairwise intermolecular energies as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the liberation of crystal stress during the phase transition is the Crystals 2018, 8, 301 2 of 9 most probable explanation for this, a full elucidation that would be valid for all thermosalient systems is still not established. Recent studies have shown that negative compressibility might be the driving force for thermosalient effect [12]. Additionally, our own theoretical calculations-performed for the first time on thermosalient materials-showed that thermosalient effect is caused by the softening of the low-energy phonon [12].…”
Section: Introductionmentioning
confidence: 71%
“…Recent studies have shown that negative compressibility might be the driving force for thermosalient effect [12]. Additionally, our own theoretical calculations-performed for the first time on thermosalient materials-showed that thermosalient effect is caused by the softening of the low-energy phonon [12]. Despite the fact that the mechanism beyond the thermosalient phenomena is not yet completely resolved, practical applications are slowly emerging.…”
Section: Introductionmentioning
confidence: 95%
“…These compounds are usually obtained in the form of crystals susceptible to physical phenomena such as polymorphism, and mechanical effects,, which may difficult their reproducible synthesis, or modify their physical properties . Thermosaliency, one of these mechanical effects, has been reported in composites, inorganic, organic, , and organometallic compounds,, and, more recently, in a spin crossover compound . It is characterized by a jumping motion, an explosive behaviour or a change in the shape of a crystal, triggered by a temperature stimulus.…”
Section: Introductionmentioning
confidence: 99%